Ensemble-Averaging Resolves Rapid Atmospheric Response to the 2017 Total Solar Eclipse - Higgins, Chad William; Drake, Stephen A.; Kelley, Jason; Oldroyd, Holly J.; Jensen, Derek D.; Wharton, Sonia (Frontiers in Earth Science, 2019)
Rapid changes in solar radiative forcing influence heat, scalar and momentum fluxes and thereby shift the trajectory of near-surface atmospheric transitions. Surface fluxes are difficult to obtain during atmospheric transitions by either bulk or eddy-covariance methods because both techniques assume quasi-stationarity in atmospheric state and require sufficiently long blocks of data, typically on the order of 10-30 min, to obtain statistically significant results. These computational requirements limit the temporal resolution of atmospheric processes that researchers can examine using traditional measurement techniques. In this paper, we present a novel observational approach to calculate surface fluxes at sub-minute temporal resolution. High-frequency data from a horizontal, log-spaced array of nine time-synchronized ultrasonic anemometers were used to perform spatial-temporal ensemble averaging and obtain eddy-covariance turbulence fluxes at unprecedented time resolution. The 2017 Great American Solar Eclipse event provided a ‘natural experiment’ to test the ensemble-observation and averaging approach. A total eclipse is energetically well-constrained and, unlike day/night transitions, is a perturbation that quickly transitions from and back to a state of significant solar forcing, providing an ideal scenario for testing the space-timescales required for surface flux calculations. Additionally, two Doppler lidars and a vertically-oriented Distributed Temperature Sensing (DTS) system provided measurements to characterize near-surface atmospheric conditions. Results show that the ensemble-averaged sensible heat fluxes converged at timescales as short as 15 s. Additional analyses show that the timescale of the connection between the surface and the atmosphere is more rapid than previous measurements have been capable of showing, and is on the order of 10 minutes or less. This experiment demonstrates that ensemble-flux measurements are capable of resolving fluctuations in surface fluxes during rapid atmospheric transitions.